Heterogeneity of Starved Yeast Cells in IF1 Levels Suggests the Role of This Protein in vivo - Galkina, Kseniia V.; Zubareva, Valeria M.; Kashko, Nataliia D.; Lapashina, Anna S.; Markova, Olga V.; Feniouk, Boris A.; Knorre, Dmitry A. (Frontiers in Microbiology, 2022)
In mitochondria, a small protein IF1 suppresses the hydrolytic activity of ATP synthase and presumably prevents excessive ATP hydrolysis under conditions of energy deprivation. In yeast Saccharomyces cerevisiae, IF1 homologues are encoded by two paralogous genes: INH1 and STF1. INH1 expression is known to aggravate the deleterious effects of mitochondrial DNA depletion. Surprisingly, no beneficial effects of INH1 and STF1 were documented for yeast so far, and the function of INH1 and STF1 in wild type cells is unclear. Here we put forward a hypothesis that INH1 and STF1 bring advantage during the fast start of proliferation after reentry into exponential growth from post-diauxic or stationary phases. We found that yeast cells increase the concentration of both proteins in the post-diauxic phase. Post-diauxic phase yeast cells formed two subpopulations distinct in Inh1p and Stf1p concentrations. Upon exit from the post-diauxic phase cells with high level of Inh1-GFP started growing earlier than cells devoid of Inh1-GFP. However, double deletion of INH1 and STF1 did not increase the lag period necessary for stationary phase yeast cells to start growing after reinoculation into the fresh medium. These results point to a redundancy of the mechanisms preventing uncontrolled ATP hydrolysis during energy deprivation.